The Link between Fiscal Decentralization and Unemployment Evidence from Indonesia: The Link between Fiscal Decentralization and Unemployment Evidence from Indonesia - Maryanti, Sri; Handra, Hefrizal; Yonnedi, Efa (ADPEBI International Journal of Business and Social Science, 2022)
The purpose of this study is to see the relationship between fiscal decentralization and unemployment in Indonesia, in this study uses panel data from 2017-2021. Where the results show that fiscal decentralization has a relationship with unemployment, but on the other hand, the level of civility and regional dependence to reduce unemployment has a negative impact, but the allocation of APBD funds is by existing regulations but still needs supervision from the central government and the area itself. Each region should seek to increase investment to reduce unemployment so that it can create jobs.